Constructing Core-Shell Co@N-Rich Carbon Additives Toward Enhanced Hydrogen Storage Performance of Magnesium Hydride - Wang, Ke; Deng, Qibo (Frontiers in Chemistry, 2020)
Magnesium hydride (MgH2) is regarded as a promising solid-state hydrogen storage material, on account of its moderate price and high gravimetric capacity. However, MgH2's inferior kinetic of hydrogen release impedes its widespread application. In this work, we use core-shell Co@N-rich carbon (CoNC) additive as catalysts to ameliorate the performances of MgH2. The surface morphologic structures and hydrogen desorption kinetics of different MgH2-CoNC composites are systematically studied. We find that MgH2-5 wt% CoNC with carbon contents of 17% (CoNC0) composites exhibit better hydrogen desorption performance. At 325°C, the MgH2-5 wt% CoNC0 composites can release up to 6.58 wt% of H2 in 5 min, which is much higher than 0.3 wt% for pure MgH2. Our results demonstrate that importing the core-shell structured catalysts can effectively enhance the hydrogen release kinetics.